Simulação da propagação de trincas por fadiga em ligas de alumínio aeronáutico sob sequências de cargas padronizadas - Montezuma, Marcos Fábio Veríssimo (2022)
This work proposes to evaluate the effect of retardation and acceleration on crack propagation in aeronautical grade aluminum alloys, subject to a history of loading of constant and variable amplitudes, through numerical simulation, using real sequences of standardized loads. For the development of the model, the concepts of fracture mechanics and fatigue are used to create an algorithm, named Propag_Lameff, developed to evaluate the effect of delay and acceleration on crack propagation. The numerical results of the model are compared with experimental results produced in the laboratory. At the end of the work, this methodology may contribute to the construction of an open-source platform related to the phenomenon of fatigue, in order to provide independent analysis of closed programs that in generally they are paid and without the possibility of expanding their functionality by the user. This methodology can be used in several areas, in addition to the aeronautical industry, where the improvement in the development of new design criteria is necessary. The crack propagation delay mechanism allows the design criteria, considering fatigue, to be optimized and realistic, avoiding excessive safety margins in the design of a component or structure